Combination of several therapeutic drugs with tetracycline to combat highly drug resistant urinary tract infection pathogens - Aftab, Ishrat Binte (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.